A new species and the shallowest record of Flabegraviera Salazar-Vallejo, 2012 (Annelida: Flabelligeridae) from Antarctica - Jimi, Naoto; Tsujimoto, Megumu; Watanabe, Kentaro; Kakui, Keiichi; Kajihara, Hiroshi (Zootaxa, 2017)
A new species of polychaete, Flabegraviera fujiae sp. nov., is described and the first report of F. mundata (Gravier, 1906) from the shallow water around Syowa Station, Antarctica, is presented. Flabegraviera fujiae sp. nov. resembles F. profunda Salazar-Vallejo, 2012 but is discriminated from the latter by having eyes and an exposed cephalic cage. The specimen of F. mundata was collected from a depth of 8 m, providing the shallowest record of this species to date.